Applying Narrative and Quantitative Models for Understanding the Sanitation Arena of Selected Gram Panchayats in a Post-TSC Era from Kerala. (December 2014) - Chathukulam, Jos; Devavrathan, S.
The Total Sanitation Campaign (TSC), a 'flagship' programme of the Government of India, has completed a decade of implementation. The TSC over the period has been able to improve human health and sanitation coverage in the country. The initial success could be attributed to 'Nirmal Gram Puraskar'. The total sanitation campaign has effectively made use of the village social structures in Kerala to solve the first generation sanitation issues. Disparities could also be seen. As the TSC is on the verge of a positive transformation to a new and broader perspective, and as the state look forward for a new dimension in sanitation concepts over the next five-year plan, it asks for a review on the coverage patterns. This would support the policy-makers to invest in edifying ideals as the nation progress from the TSC to 'Nirmal Bharat Abhiyan'. The broad objective of the study thus is to assess the impact of sanitation and hygiene coverage in the state. For measuring the outcomes and relative performance in terms of total sanitation provision, seven selected Gram Panchayats of Kozhikode district are considered. To arrive at a robust scenario, a synthesis of a narrative and statistical model was used. An innovative measurement framework known as 'Total Sanitation Index' was developed. The index was formulated for comprehending the relative positions of each Panchayat in terms of total sanitation and the results were presented.